Determinants of stock returns in BRICS countries / Muhammad Naim Ramli, A’tiqah Rashidah Abu Samah and Roseziahazni Abdul Ghani - Ramli, Muhammad Naim; Abu Samah, A’tiqah Rashidah; Abdul Ghani, Roseziahazni (2017)
This paper investigates on determinants of stock return for BRICS countries. The relationship between stock market return and macroeconomic variables can be used to make nation’s macroeconomic policies and the performance of stock return can be a benchmark for a country to highlight the country is in well economic condition or not. This paper employs the test on pooled data from 2011 to 2015 on monthly basis, to examine the factors that affect stock return the most. Exchange rate, money supply, inflation and trade are selected as the macroeconomics variables factors that affect stock market return. All these factors lead to strong significant relationship towards stock market return by present or doing well towards each factor.